Prevention of Chemotherapy-related Oral Mucositis by Topical Timolol: A Prospective Randomized, Double-blind, Placebo-controlled Clinical Trial in Cancer Patients - Saghafi, Fatemeh; Shaker-Ardakani, Fatemeh; Nabi-Meybodi, Mohsen; Vahedian-Ardakani, Hassan-Ali; Sahebnasagh, Adeleh (Recent Advances in Inflammation & Allergy Drug Discovery, 2025)
<span class=
Keywords: Chemotherapy-induced mucositis